2020
DOI: 10.1029/2020je006479
|View full text |Cite
|
Sign up to set email alerts
|

Photon‐Stimulated Desorption of MgS as a Potential Source of Sulfur in Mercury's Exosphere

Abstract: Mercury has a relatively high sulfur content on its surface, and a signal consistent with ionized atomic sulfur (S+) was observed by the fast ion plasma spectrometer (FIPS) instrument on the MESSENGER spacecraft. To help confirm this assignment and to better constrain the sources of exospheric sulfur at Mercury, 193 nm photon‐stimulated desorption (PSD) of neutral sulfur atoms (S0) from MgS substrates was studied using resonance‐enhanced multiphoton ionization (REMPI) spectroscopy and time‐of‐flight (TOF) mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 60 publications
(100 reference statements)
1
6
0
Order By: Relevance
“…The inset shows the final E (t r ) energy as a function of excited state resonance time, t r . Figure reproduced from Schaible et al (2020) with permission in the range of about 4-10 eV. Photo-excitations invoke an electronic transition, which must be localized at the surface, leading to an anti-bonding state that results in the release of the excited atom (Na, K, .…”
Section: Mechanism Of Photon Stimulated Desorptionmentioning
confidence: 99%
See 2 more Smart Citations
“…The inset shows the final E (t r ) energy as a function of excited state resonance time, t r . Figure reproduced from Schaible et al (2020) with permission in the range of about 4-10 eV. Photo-excitations invoke an electronic transition, which must be localized at the surface, leading to an anti-bonding state that results in the release of the excited atom (Na, K, .…”
Section: Mechanism Of Photon Stimulated Desorptionmentioning
confidence: 99%
“…4). Experimental data for H 2 O desorption can be fit using this form with a bi-modal distribution consisting of a low temperature thermal component (matching the substrate temperature) and a high temperature 'suprathermal' component due to direct desorption along the normal component (Bennett et al 2016;DeSimone and Orlando 2014;Zimmermann and Ho 1994;Schaible et al 2020). Since this distribution function includes the intrinsic physics of the desorption process, this is often used as an experimental fitting procedure in addition to the Weibull distributions discussed below.…”
Section: Psd Velocity Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical estimates of the S column density in Mercury's exosphere (6 × 10 7 cm −2 from Wurz et al 2010; 10 9 cm −2 from Berezhnoy 2018; 2 × 10 10 cm −2 from Morgan and Killen 1997; and 2 × 10 13 cm −2 from Sprague et al 1995) are inconsistent. Recent laboratory experiments suggest that photon-stimulated desorption of S from MgS, a proxy for the global form of S on Mercury's surface, may provide a global, additional source of S at low altitudes of Mercury's exosphere (Schaible et al 2020). Doressoundiram et al (2009) reported upper limits for the Mercury's exosphere of silicon (Si) of 5 × 10 10 cm −2 ) from the European Southern Observatory -New Technology Telescope in La Silla, Chile.…”
Section: Missing Speciesmentioning
confidence: 99%
“…Also needed are experiments that refine the yields, cross sections, and threshold energy for photon-stimulated desorption (e.g. Schaible et al 2020) and electron-stimulated desorption (e.g. McLain et al 2011).…”
Section: Laboratory Measurementsmentioning
confidence: 99%